Where Have All the Turtles Gone, and Why Does It Matter?. (12th September 2018) - Lovich, Jeffrey E; Ennen, Joshua R; Agha, Mickey; Gibbons, J Whitfield
Abstract: Of the 356 species of turtles worldwide, approximately 61% are threatened or already extinct. Turtles are among the most threatened of the major groups of vertebrates, in general, more so than birds, mammals, fishes or even the much besieged amphibians. Reasons for the dire situation of turtles worldwide include the familiar list of impacts to other species including habitat destruction, unsustainable overexploitation for pets and food, and climate change (many turtles have environmental sex determination). Two notable characteristics of pre-Anthropocene turtles were their massive population sizes and correspondingly high biomasses, the latter among the highest values (over 855 kilograms per hectare) ever reported for animals. As a result of their numerical dominance, turtles have played important roles as significant bioturbators of soils, infaunal miners of sea floors, dispersers and germination enhancers of seeds, nutrient cyclers, and consumers. The collapse of turtle populations on a global scale has greatly diminished their ecological roles.